2023
DOI: 10.3892/ol.2023.13762
|View full text |Cite
|
Sign up to set email alerts
|

Role of RUNX2 in breast cancer development and drug resistance (Review)

Abstract: Breast cancer is the most common malignancy and ranks second among the causes of tumor-associated death in females. The recurrence and drug resistance of breast cancer are intractable due to the presence of breast cancer stem cells (BCSCs), which are adequate to initiate tumor formation and refractory to conventional remedies. Runt-related transcription factor 2 (RUNX2), a pivotal transcription factor in mammary gland and bone development, has also been related to metastatic cancer and BCSCs. State-of-the-art … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 139 publications
(142 reference statements)
1
2
0
Order By: Relevance
“…Unraveling the complicate immune system‐related apoptotic signaling in different epithelia falls beyond the scope of our study. Yet, our findings in the mammary tissue associating CT with decreased cytoplasmic and increased nuclear p21, and the downregulation of c‐Myc and Runx2 are in line with this notion 37–40 . In agreement with this are also the downregulation of Klf4 in the lung and of Runx3 in the squamous stomach epithelium 41 .…”
Section: Discussionsupporting
confidence: 88%
“…Unraveling the complicate immune system‐related apoptotic signaling in different epithelia falls beyond the scope of our study. Yet, our findings in the mammary tissue associating CT with decreased cytoplasmic and increased nuclear p21, and the downregulation of c‐Myc and Runx2 are in line with this notion 37–40 . In agreement with this are also the downregulation of Klf4 in the lung and of Runx3 in the squamous stomach epithelium 41 .…”
Section: Discussionsupporting
confidence: 88%
“…We analyzed a total of 11 genes interacting with NGR1 predicted targets and breast cancer target genes based on online databases, mainly enriched in the AGE-RAGE signaling pathway, which has been shown to correlate with ferroptosis-related factors in periodontitis disease [ 17 ], the AGE-RAGE signaling pathway has been shown to be associated with ferroptosis-related factors, and it has been reported in the literature that there is a protein-regulatory relationship with NGR1 and RUNX2 in osteoblast differentiation [ 16 ] Our molecular docking results also demonstrated the existence of binding sites for NGR1 and RUNX2. It has been reported in the literature that RUNX2 is able to recruit the NuRD (MTA1)/CRL4B complex and accelerate breast cancer progression and bone metastasis [ 18 ] and RUNX2 is also associated with breast cancer drug resistance [ 19 ]. Inhibition of RUNX2 expression is a new perspective to prevent breast cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mutations in the RUNX2 gene have been associated with cleidocranial dysplasia, a skeletal disorder characterized by abnormal bone development [14]. RUNX2 has also been implicated in developing and progressing breast and prostate cancer [15,16]. Te function of RUNX2 is regulated by a variety of signaling pathways, including the Wnt, BMP, FGF, Shh, and PTH pathways [4], and RUNX2 activity is also modulated by posttranslational modifcations, including phosphorylation, acetylation, and SUMOylation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that RUNX2 may also have a role in cancer. In particular, RUNX2 has been found to be overexpressed in various types of cancer, including breast, prostate, and lung cancer [15,26,27]. RUNX2 is thought to promote tumor growth and metastasis by inducing the expression of genes involved in angiogenesis, cell migration, and invasion.…”
Section: Introductionmentioning
confidence: 99%